2020
DOI: 10.1038/s41598-020-59354-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating thyroid hormone disruption: investigations of long-term neurodevelopmental effects in rats after perinatal exposure to perfluorohexane sulfonate (PFHxS)

Abstract: Thyroid hormones are critical for mammalian brain development. Thus, chemicals that can affect thyroid hormone signaling during pregnancy are of great concern. Perfluorohexane sulfonate (PFHxS) is a widespread environmental contaminant found in human serum, breastmilk, and other tissues, capable of lowering serum thyroxine (T4) in rats. Here, we investigated its effects on the thyroid system and neurodevelopment following maternal exposure from early gestation through lactation (0.05, 5 or 25 mg/kg/day PFHxS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 78 publications
(110 reference statements)
0
26
0
1
Order By: Relevance
“…On the other hand, a study performed on dams exposed to PFHxS reported no statistically significant effects on thyroid gland weights and histopathology ( 54 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a study performed on dams exposed to PFHxS reported no statistically significant effects on thyroid gland weights and histopathology ( 54 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the placentas of humans and rats show anatomical similarities with a discoid shape and hemochorial type of fetal-maternal interface, however, disparities exist regarding the histological structure and the function of the yolk sac ( 31 ). Finally, important considerations are on the assessment of brain development in humans and in experimental animals, respectively ( 32 ).…”
Section: The Hypothesis Of Fetal Programmingmentioning
confidence: 99%
“…maze) can be evaluated ( Table 1 ). However, no measure of brain development in an experimental animal directly translates to IQ in humans ( 32 ). Furthermore, it is important to notice that many methodological considerations exist when the role of maternal thyroid disease in relation to fetal brain development is assessed in humans and in an experimental design.…”
Section: The Hypothesis Of Fetal Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemicals that can affect thyroid hormone signaling during pregnancy are an important issue in this field [ 17 ], since thyroid hormones play a critical role in fetal development. Ramhoj et al [ 18 ] studied the effects of perfluorohexane sulfonate (PFHxS), a widely used environmental chemical found in breast milk, on fetal brain development. PFHxS has been proven to lower serum thyroxine in a rat model [ 19 ].…”
Section: Environmental Factors: Thyroid-disrupting Chemicalsmentioning
confidence: 99%